Atividade antibacteriana dos extratos dos frutos de Coussapoa asperifolia subsp. magnifolia (Trécul) contra Aeromonas hydrophila e fracionamento do extrato metanólico - Andrade, Jaqueline Inês Alves de (2009)
The fish farming is a promising sector for food production, however, there are still several bottlenecks to its development. One of these impediments is the fish’s health. They are few studies regarding the treatment forms that can be used on fish farming systems, mainly about diseases caused by bacterial agents. This is a great problem, because many of the fish farming diseases are of bacterial aetiology, and they are acquiring more and more resistance to the antibiotics traditionally used. One of the species that causes great mortalities in fish farming is Aeromonas hydrophila, microorganism that is becoming more and more resistant to the antibiotics used commonly due to its indiscriminated use. Consequently, the interest for biologically actives natural products with the intention of use them as prophylaxis and in fish diseases treatment has been increased in the last years. Therefore, the aim of this work was to evaluate the antibacterial activity of dicloromethanic (DCM), methanolic (MeOH) and aqueous (H2O) extracts of Coussapoa asperifolia subsp. magnifolia fruits against Aeromonas hydrophila and to fractionate the most active extract. The antibacterial activity assays were accomplished, in duplicate, using the agar diffusion method by well technique and bioautography. The minimum inhibitory concentration (MIC) determination was made by macrodilution and the minimum bactericidal concentration (MBC), from MIC. The DCM extract didn't show antibacterial activity, however, the MeOH and H2O extracts showed activity against A. hydrophila. Between the two active extracts, the MeOH was chosen for subsequent fractioning, due to the characteristics of the molecules present in it. The MIC and MBC for the MeOH extract were 4 mg/mL and 32 mg/mL, respectively and showing both bacteriostatic and bactericidal activities. The fractionation of this extracts began by liquid-liquid partition using DCM, ethyl acetate (AcOEt), buthanol (BuOH) and H2O, as solvents. Then, a new assay to evaluate the antibacterial activity of those phases was accomplished and all phases showed activity, however, with different intensities, and due to their molecular characteristics and mass amount, AcOEt phase was chosen for the subsequent fractioning. So, the AcOEt phase fractionation was performed by using Florisil column chromatography and DCM, AcOEt and MeOH gradient, yielding 86 fractions, which were combined after thin layer chromatography comparison totalizing 10 fractions. The antibacterial test was made with the last fractions containing enough mass to follow the fractionation, but showed no activity. Thus, tests were carried out bioautography assay with the phase AcOEt (original), to determine whether there was a possibility of the active substances have been held in the column, and if still had the possibility of synergism occurring between all the fractions and, by the results obtained, both possibilities were discarted. Thus, what may have happened is that the choice of stationary or mobile phases was incorrect, yielding the degradation of the active molecules. Other fractionation methods should be carried out with the fruit methanolic extract of C. asperifolia subsp. magnifolia in order to isolate the antibacterial molecules.